Mode Recognition of Hybrid Dynamical System A Bond Graph Approach - Nadia ZANZOURI (International Journal of Applied Methods in Electronics and Computers, 2016)
In this paper, we develop a methodology to identify the current mode of Hybrid Dynamical System (HDS) based on Bond Graph (BG) approach.The technique is also able to detect and to isolate the continuous and discrete faults affected the system. Analytical Redundancy Relations (ARR) based methods are used to generate the fault indicators namely residuals for the identification of  the current mode.An illustrative example shows the efficiencies of the proposed approach.